A chromosome-level genome assembly of beet webworm, Loxostege sticticalis Linnaeus (Lepidoptera: Pyralidae) - Yu Zhang; Yanyan Li; Yanmin Shan; Haibin Han; Penghua Bai; Linbo Xu; Qing Zhao; Ningyun Liu; Yuanyuan Wang; Ying Wang; Liwa Ga; Lei Xu; et al. (Scientific Data)
Abstract The beet webworm, Loxostege sticticalis Linnaeus (Lepidoptera, Pyralidae), is a major pest in agriculture and livestock production. However, the L. sticticalis genome has not yet been sequenced, limiting exploration of its biological features and population genetics. In this study, the genome of L. sticticalis was sequenced on the Illumina Novaseq. 6000 and PacBio Sequel II platforms, and chromosome conformation capture (Hi-C) methods were used to generate the high-quality chromosome-level genome, assessed at 98.7% by the Benchmarking Universal Single-Copy Orthologs (BUSCO) tool. The L. sticticalis genome showed an assembly of 485.9 Mb with a contig N50 of 16.4 Mb, a scaffold N50 of 16.6 Mb, and a GC content of 37.85%, with over 98.67% of the assembled bases located on 31 chromosomes. Repeat sequences accounted for 41.71% of the genome and 15 913 protein-coding genes were identified. Comparison of the genome of L. sticticalis with other closely related species indicated high chromosomal synteny. The sequencing of this genome contributes to research on the genetics and evolution of the Lepidoptera.